Prolonged Hospital Stays in Continuous Ambulatory Peritoneal Dialysis (CAPD) Patients: The Role of Comorbid Conditions - Nurjaya Adinugroho; Eriawan Agung Nugroho; Sofyan Rais Addin (HM Publisher, 2025)
Background: Continuous ambulatory peritoneal dialysis (CAPD) is a widely used treatment for end-stage renal disease (ESRD), but it is associated with frequent hospitalizations that can significantly impact patients' quality of life and increase healthcare costs. This study aimed to investigate the influence of comorbid conditions on the length of hospital stay (LOS) in CAPD patients. Methods: A retrospective cohort study was conducted on CAPD patients admitted to Dr. Kariadi General Hospital Semarang between January 1st, 2023, and December 31st, 2023. Data on demographics, comorbidities, and LOS were extracted from medical records. The Charlson Comorbidity Index (CCI) was used to assess comorbidity burden. Multivariable linear regression analysis was performed to identify predictors of prolonged LOS, defined as exceeding the median LOS. Results: The study included 52 CAPD patients with a median LOS of 18 days (range: 1-72 days). Patients with comorbidities had a significantly longer LOS compared to those without comorbidities (20.25 ± 12.88 days vs. 12.50 ± 3.63 days, p = 0.045). The presence of comorbidities was significantly associated with prolonged LOS (odds ratio [OR] 2.87, 95% confidence interval [CI] 1.15-7.16, p = 0.023), as were older age (OR 1.05, 95% CI 1.01-1.09, p = 0.012) and peritonitis as the primary reason for hospitalization (OR 3.54, 95% CI 1.38-9.08, p = 0.008). Conclusion: Comorbid conditions are significant contributors to prolonged hospital stays in CAPD patients. These findings underscore the importance of effectively managing comorbidities in this population to optimize healthcare resource utilization and improve patient outcomes.